2022
DOI: 10.1002/acm2.13522
|View full text |Cite
|
Sign up to set email alerts
|

Replacing gamma knife beam‐profiles on film with point‐detector scans

Abstract: Purpose Detector arrays and profile‐scans have widely replaced film‐measurements for quality assurance (QA) on linear accelerators. Film is still used for relative output factor (ROF) measurements, positioning, and dose‐profile verification for annual Leksell Gamma Knife (LGK) QA. This study shows that small‐field active detector measurements can be performed in the easily accessed clinical mode and that they are an effective replacement to time‐consuming and exacting film measurements. Methods Beam profiles a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…They reported that the W2 and film agreed to within 0.5% for all measurements. Rudek et al 13 . intercompared the W2, a PTW microdiamond detector and Gafchromic EBT3 film for measurement of relative profiles for the Gamma Knife.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…They reported that the W2 and film agreed to within 0.5% for all measurements. Rudek et al 13 . intercompared the W2, a PTW microdiamond detector and Gafchromic EBT3 film for measurement of relative profiles for the Gamma Knife.…”
Section: Resultsmentioning
confidence: 99%
“…They reported that the W2 and film agreed to within 0.5% for all measurements. Rudek et al 13 intercompared the W2, a PTW microdiamond detector and Gafchromic EBT3 film for measurement of relative profiles for the Gamma Knife. They did not quantify the extent to which the relative profiles agreed with one another but did report how well the measured full-width half -maximum and penumbra width agreed with the treatment planning system.…”
Section: 33mentioning
confidence: 99%
See 3 more Smart Citations